2004
DOI: 10.1111/j.1752-7325.2004.tb02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Dentate Status of Adults, Use of Dental Health Services, and Achievement of National Dental Health Goals in Denmark by the Year 2000

Abstract: Compared to similar studies carried out in 1987 and 1994, the present survey indicates a positive trend of improved dentate status in adult Danes in general and regular use of dental health services increased considerably over time. The WHO goals for better dental health by the year 2000 were achieved for 35-44-year-olds, whereas the goal of more people with functional dentitions at age 65 years or older was not achieved. It remains a challenge to the Danish dental health system to help even out the social ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
149
1
27

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 14 publications
14
149
1
27
Order By: Relevance
“…While these treatment measures have been on the decrease for a long time in Sweden, the provision with crowns continues to rise and the endodontic treatments per patient remain constant in Germany [18,23,52]. In contrast to Denmark, which introduced preventive benefits for adults into its social benefits catalogue [36], no such step has been taken thus far in Germany, since the self-administration bodies of the dentists and sickness funds have so far failed to reach an agreement on the corresponding benefits.…”
Section: Possible Reasons For Variations In System Performancementioning
confidence: 99%
See 1 more Smart Citation
“…While these treatment measures have been on the decrease for a long time in Sweden, the provision with crowns continues to rise and the endodontic treatments per patient remain constant in Germany [18,23,52]. In contrast to Denmark, which introduced preventive benefits for adults into its social benefits catalogue [36], no such step has been taken thus far in Germany, since the self-administration bodies of the dentists and sickness funds have so far failed to reach an agreement on the corresponding benefits.…”
Section: Possible Reasons For Variations In System Performancementioning
confidence: 99%
“…'Regular dental attendance' is chosen as the key indicator for this area because many studies show a strong relationship between the regular use of dental services and improved dental health [23,26,[36][37][38]. Studies with divergent results concerning the relationship between regular checkups and oral health status are hardly reliable because, in most instances, DMFT/DMFS values for oral health outcome were used and only small numbers of teenagers were studied for short periods [39][40][41].…”
Section: Possible Reasons For Variations In System Performancementioning
confidence: 99%
“…These studies provide valuable information about background related changes in oral health conditions at certain points of time. It has for example been shown that edentulousness has a much lower incidence now than 30 years ago (Petersen et al, 2004;Holst, 2008). The main explanations for this are improved standard of living, availability of fluoride toothpaste and more accessible dental services.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns países desenvolvidos apresentam uma tendência de declínio de perda dentária entre adultos, que se refletirá na população idosa nos próximos anos, mas as iniquidades sociais, no que diz respeito à saúde bucal, ainda persistem mesmo em países que têm programas avançados de saúde pública nesta área 7,8,9 .…”
unclassified